Analysis Of Accounting Information System In Merchantability Inventory With Fifo And Average Method At Pt. Main Dennis - Kartinah, Dwi (Publisher Cv. Inara, 2021)
The author chose PT Dennis Utama as the object of research. PT Dennis Utama is a company that distributes food ingredients, namely rice. Researchers obtained primary data from interviews by the sales department of PT Dennis Utama and secondary data from literature studies using flowchart and descriptive analysis techniques. The analysis used is the FIFO and AVERAGE methods. The aim is to find out the results of the analysis of the merchandise inventory accounting information system at PT Dennis Utama with the FIFO and AVERAGE methods. The results of this study are in the form of flowcharts and descriptive results. Based on the results of the research that PT Dennis Utama uses the FIFO and AVERAGE methods which are quite good, there are only a few shortcomings, namely sometimes there is still a little buildup of goods so that merchandise is damaged and also the company has not implemented a computerized system in its company activities.